1991
DOI: 10.1002/rcm.1290051004
|View full text |Cite
|
Sign up to set email alerts
|

Massive cluster impact mass spectrometry: A new desorption method for the analysis of large biomolecules

Abstract: A new ion desorption method is described that utilizes a primary beam of massive, multiply charged cluster ions to generate secondary ions of peptides in a glycerol matrix. The massive cluster ion beam is generated via electrohydrodynamic emission using a 1.5 M solution of ammonium acetate in 30% aqueous glycerol. Negative ion spectra of peptides obtained using this technique show greatly decreased relative intensities for fragment ions and 'chemical noise' background when compared to spectra obtained using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 32 publications
1
81
0
Order By: Relevance
“…desorption of only molecular-level superficial sample, little damage accumulation and self-cleaning effect, [12][13][14]19 contamination free by using evaporative projectiles, soft ionization although not fragment-free, no need to use a matrix, and extremely high tolerance to the presence of salts. Since the beam of electrospray droplet projectiles is $3 mm in diameter, the spatial resolution is practically non-existent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…desorption of only molecular-level superficial sample, little damage accumulation and self-cleaning effect, [12][13][14]19 contamination free by using evaporative projectiles, soft ionization although not fragment-free, no need to use a matrix, and extremely high tolerance to the presence of salts. Since the beam of electrospray droplet projectiles is $3 mm in diameter, the spatial resolution is practically non-existent.…”
Section: Discussionmentioning
confidence: 99%
“…Mahoney and co-workers carried out pioneering work in generating multiply charged massive glycerol clusters with $200 charges via electrohydrodynamic emission in vacuum using a 1.5 M solution of ammonium acetate in glycerol. [12][13][14][15] The masses of the projectile, 10 6 -10 7 u, may be the largest among the SIMS clusters developed so far. This method was found to afford extremely soft desorption conditions for peptide and protein ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20) Mahoney et al reported that c-ions can be observed in negative-ion FAB mass spectra of peptides with a glycerol matrix. 40) Furthermore, the observation of c-ions was reported by Vorst et al by using plasma desorption mass spectrometry (PD MS) with nitrocellulose matrices. 40) FAB, LSIMS and PD can be referred to as ESDI, a type of high-translational energy particle impinging method, and ESDI results in locally electronic excitation due to keV energy collision on the target molecules.…”
Section: Observation Of C-ions In Energy-sudden Desorption/ionizationmentioning
confidence: 93%
“…Besides the fundamental knowledge that can be gained from the study of a significantly new range of projectiles, electrosprayed nanodroplets may intensify the size-related advantages of gas cluster ions for certain surface engineering applications and for secondary mass spectrometry of large molecules. Although Mahoney et al (1991) and Mahoney (1998) previously utilized droplets and clusters of glycerol as projectiles for secondary ion mass spectrometry and surface cleaning, the recently reported sputtering rates and surface modifications of materials as hard as GaN,SiC,or B 4 N represent a qualitative advancement of nanodroplet beams. The current development is rooted in the improved understanding of electrospraying, especially in the area of nanodroplet generation, which is largely due to the work of Fern andez de la Mora and collaborators on both the physics of electrosprays (Fern andez de la Mora and Loscertales 1994), and the use of highly conducting liquids including ionic liquids (Gamero-Castaño and Fern andez de la Mora 2000; Garoz et al 2007).…”
Section: Introductionmentioning
confidence: 99%